Synthesis of alpha-D-Glcp-(1-3)-alpha-D-Galf-(1-2)-alpha-L-Rhap constituent of the CPS of Streptococcus pneumoniae 22F. Effect of 3-O-substitution in 1,2-cis alpha-D-galactofuranosylation - Gola, Gabriel (2014)
The synthesis of the trisaccharide a-D-Glcp-(1-3)-a-D-Galf-(1-2)-L-Rhap (3) constituent of Streptococcus pneumonia 22F was achieved with complete diastereoselectively. This is the first example of a synthesis of an internal a-D-Galf containing oligosaccharide of a pathogen microorganism. Allyl α-D-galactofuranoside, used as novel precursor of the internal Galf, allowed the introduction of an orthogonal group at O-3. The trichloroacetimidate method was used for the construction of 1,2-cis a-D-galactofuranosyl linkage. The influence of the 3-O-substituent (PMB, Bz, PFBz, PMBz, TIPS) was evaluated in benzylated galactofuranosyl trichloroacetimidate donors in terms of yield and selectivity of a-D-Galf-(1-2)-a-L-Rhap product as well as donor rearrangement by-product. Complete stereoselectivity was observed with all protecting groups used in Galf donor, but the 3-O-benzoyl substitution gave the best yield. Protective groups were also evaluated in rhamnoside acceptor, benzyl substitution was a requirement for complete stereoselectivity.